2019
DOI: 10.1093/carcin/bgz093
|View full text |Cite
|
Sign up to set email alerts
|

PAUF/ZG16B promotes colorectal cancer progression through alterations of the mitotic functions and the Wnt/β-catenin pathway

Abstract: Pancreatic adenocarcinoma upregulated factor (PAUF), also known as ZG16B, was previously found in the secretome of metastatic colorectal cancer cells. Here, we demonstrated the presence of PAUF at the intracellular level and its multiple effects on cancer progression. An initial decline of PAUF expression was observed at early stages of colorectal cancer followed by an increase at the metastatic site. PAUF was located at different cellular compartments: membraneassociated vesicles, endosomes, microtubule-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Zymogen granule protein 16 (ZG16) is a soluble protein that is expressed only in epithelial cells of the small intestine, rectum, and colon [36]. Studies have shown that ZG16 is downregulated in colorectal cancer, which is consistent with the results of our analysis [37][38][39]. However, the detailed molecular mechanism of ZG16 in colorectal cancer is still unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Zymogen granule protein 16 (ZG16) is a soluble protein that is expressed only in epithelial cells of the small intestine, rectum, and colon [36]. Studies have shown that ZG16 is downregulated in colorectal cancer, which is consistent with the results of our analysis [37][38][39]. However, the detailed molecular mechanism of ZG16 in colorectal cancer is still unknown.…”
Section: Discussionsupporting
confidence: 89%
“…In general, the results are in line with multiple previous studies, which indicated that loss of ZG16 expression may make a great difference in CRC development and worse OS. [18][19][20][21] In fact, the TNM system based on the depth of tumor invasion (T), the number of affected lymph nodes (N), and the presence of metastasis (M) remains the most common prognostic indicator for stratifying patients. However, survival rates are highly heterogeneous for even patients who are within the same TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Among the nine genes with biased expression in the earlier stage P8-1 ( Supplementary Table 6), MSMB (microseminoprotein beta, Figure 6d) is one of the most abundant proteins in semen (123)(124)(125) and it has been used for diagnosis of prostate cancer (126). ZG16B/PAUF (pancreatic adenocarcinoma-upregulated factor, Figure 6D) is a secreted protein with crucial role in pancreatic ductal adenocarcinoma (PDAC) (127)(128)(129)(130), as well as other cancer types including epithelial ovarian cancer (131), cervical carcinoma (132), colorectal cancer (133) and oral squamous cell carcinoma (134). KLK5 (Kallikrein-related peptidases 5, Figure 6D) is in the same gene family as the prostate-specific antigen KLK3, exerts key modulatory effects on many cancers (135)(136)(137)(138)(139) and it is selectively inhibited by SPINK, a family of serine peptidase inhibitor kazal type, which bind to their target serine proteases and inhibit their proteolytic function (140)(141)(142)(143)(144)(145).…”
Section: The Power Of Single-cell Rna Sequencing In Csf Samples For Tmentioning
confidence: 99%